Design of pectin-sodium alginate based films for potential healthcare application: Study of chemico-physical interactions between the components of films and assessment of their antimicrobial activity. (10th February 2017) - Nešić, Aleksandra; Onjia, Antonije; Davidović, Sladjana; Dimitrijević, Suzana; Errico, Maria Emanuela; Santagata, Gabriella; Malinconico, Mario
Abstract: In this study, pectin based films including different amounts of sodium alginate were prepared by casting method. All the films, with and without polyglycerol as plasticizer, were crosslinked with zinc ions in order to extend their potential functionality. The development of junction points, occurring during the crosslinking process with zinc ions, induced the increasing of free volume with following changing in chemico-physical properties of films. The inclusion of alginate in pectin based formulations improved the strength of zinc ions crosslinking network, whereas the addition of polyglycerol significantly improved mechanical performance. Finally, zinc-crosslinked films evidenced antimicrobial activity against the most common exploited pathogens: Staphylococcus Aureus, Escherichia Coli and Candida Albicans . These results suggest that zinc-crosslinked based films can be exploitable as novel bio-active biomaterials for protection and disinfection of medical devices.